Part. 1 (2005, 2005)
This textbook consists of 2 chapters devoted to crystallography and mineralogy. The textbook is prepared at the TPU Mineralogy and Petrography Department. It is recommended (intended) for foreign students studying according to the Bachelor Degree Program in Applied Geology at Tomsk Polytechnic University.